Prevalence of metallo-Beta-lactamase producing Pseudomonas aeruginosa in a tertiary care at Hospital Kuala Lumpur, Malaysia - Idris, Siti Nur Atiqah (2016)
Introduction: Carbapenems are the primary choice of treatment for nosocomial Pseudomonas aeruginosa infections. However, the emergence of carbapenem resistance due to the production of metallo-β-lactamases (MBLs) is a worldwide concern. Objective: To determine the prevalence of P. aeruginosa producing metallo-β-lactamase isolated from clinical isolates at Hospital Kuala Lumpur (HKL), Malaysia. Method: A total of 83 P. aeruginosa isolates were collected and tested for metallo-β-lactamase production using a phenotypic combined disc method and genotypic detection by polymerase chain reaction (PCR) and random amplified polymorphic DNA (RAPD). Results: Of all the isolates, 52% were found to be imipenem resistant P. aeruginosa and from that, 65% of the isolates showed positive result by phenotypic imipenem-EDTA combined disc test in which there were an increase in inhibition zone on imipenem with EDTA as compared to imipenem alone. MBL genes were detected from polymerase chain reaction (PCR) in 35% of total isolates (strains producing blaIMP were 45% followed by blaVIM, blaSPM and blaGIM with 34%, 14% and 7%, respectively. RAPD analysis showed a total of 8 clusters among the 83 P. aeruginosa clinical isolates. Conclusion: Our study highlight that blaIMP and blaVIM were predominantly present among the P. aeruginosa clinical isolates from Hospital Kuala Lumpur. Keywords: Pseudomonas aeruginosa, imipenem resistance, metallo-β-lactamases (MBLs), blaIMP, blaVIM, blaSPM and blaGIM.